Genentech : introduction of the first therapy for acute stroke - Glazer, Rashi; Bressler, John; Liu, David; Lee, Tom; Margulies, Michael; Vontz, Greg (London : SAGE Publications Ltd, 2017)
Stroke ranks as the third leading cause of death in the U.S. After a series of clinical trials, Genentechs Activase, a drug for preventing the blood clots that cause strokes, was approved by the FDA. One of the most significant issues Genentech faced was educating the market on stroke therapy with Activase. The stroke market not only included the hospitals and physicians, but also patients as well. Since the therapy was time dependent, patients need to know a new therapy was available for which they had to seek prompt medical attention. This clearly pointed to the need for public education on the signs and symptoms of stroke and the treatment benefits of Activase. The need to educate patients and physicians created a strategic challenge. In what sequence should Genentech educate the marketphysicians first and then the public, the reverse order, or both simultaneously? What were the costs to implement these strategies?
Originally published in Glazer, R., Bressler, J., Liu, D., Lee, T., Margulies, M., & Vontz, G. (2007). Genentech: Introduction of the first therapy for acute stroke. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Genentech, Inc; Marketing; New products; Pharmaceutical industry